Analisis Pertumbuhan dan Kandungan Pb Hijauan Pakan Ternak di Lahan Pasca Tambang Timah - Tri Lestari; Rutfi Puji Astuti; Sandi Sandi; Wiarti Winarti; Della Della; Gusva Yetti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Lestari T, Astuti RP, Sandi S, Winarti W, Della D, Yetti G. 2022. Analysis of growth and pb content of forage animal feed in post tin mining land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1033-1040. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Mining activities can cause a decrease in soil productivity. Pb is one of the metals commonly found in post-tin mining areas. The purpose of the study was to determine the analysis of growth and metal content of Pb contained in forage animal feed. The green growth analysis of animal feed was carried out using an experimental method using a randomized block design (RAK) by using several improvements. Analysis of feed quality and Pb content by carrying out various combinations of animal feed mixtures with forage base materials cultivated in post-tin mining land. The results showed different growth responses of animal feed to the provision of several improvements. Giving growth regulators PGR gives better plant growth. Giving mycorrhizae can reduce the use of NPK fertilizers. Analysis of the quality and content of Pb showed the results were on the threshold. Analysis of animal feed cultivated in post-tin mining shows that it is safe for livestock consumption.